A cognitive linguistic approach to the emotion of anger in the Old Testament - Kotzé, Zacharias (HTS teologiese studies, 2004)
This article reviews several approaches to the study of anger in the Old Testament. It focuses on the use of methodology in these trends with specific reference to the common neglect of Classical Hebrew terminology and expressions relating to the emotion of anger. Such styles lead to an impoverished understanding of the ideal cognitive model of anger as reflected in Classical Hebrew. By contrast, the few recent cognitive linguistic studies on the same subject prove to be far more successful in giving a detailed account of the ancient Israelite conceptualisation of this emotion.